Metodologia automatizada para descrever a cobertura de sinal móvel em rodovias: estudo de caso considerando incerteza de dados - Röpke, Leonardo Luís (2023)
Due to the wide geographical distribution or the existence of extensive road infrastructure, ensuring that mobile operators provide adequate service along roads can be challenging. An automated methodology for describing and evaluating mobile network signal coverage on roads can help government and mobile operators effectively plan actions to improve network signal coverage. In this work, an automated methodology is proposed to describe and allow the evaluation of mobile network signal coverage on roads using vehicle tracking data. The proposed approach aggregates data samples obtained through an online vehicle tracking system using a spatio-temporal criterion. The resulting output of this aggregation process is a road map with a gradient color scheme to indicate the signal availability and reliability of this information. As the traffic is dynamic and the traffic data does not follow a uniform distribution, the uncertainty measure associated with the map indicates the reliability of the information provided. As a case study, we used a set of private travel data in southern Brazil collected through a vehicle tracking service. The proposed methodology makes it possible to analyze the availability of the signal on the roads, within the geographic area delimited by the data, and allows the use of filters by period or road name, for more specific analyses. Finally, with the use of the proposed methodology and the available data, it could be concluded that the availability of the signal on the roads in southern Brazil is above the minimum established by Draft Law 1721/2019, which establishes the obligation to offer telephone services mobile and mobile Internet services along federal roads.